Mediastinal Extranodal Follicular Dendritic Cell Sarcoma: A Case Report - Arbil Acikalin (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Follicular dendritic cell sarcoma is a spindle cell neoplasm, originating from follicular dendritic cells. It frequently presents in lymph nodes. Occasionally, it occurs in extranodal regions like head and neck, mediastinum, gastrointestinal system. We present a 50 years old woman with mediastinal and metastatic follicular dendritic cell sarcoma with clinical and pathological findings. Follicular dendritic cell sarcoma is usually under-recognized because of the misleading histomorphology and the rarity of this tumor. Hence, this tumor has specific immunohistochemical markers, it is important to keep in mind this tumor in differential diagnosis of spindle cell tumors. [Cukurova Med J 2014; 39(2.000): 377-382]